Pengaruh Citra Merek Dan Kualitas Produk Teh Botol Sosro Terhadap Loyalitas Pelanggan - Wijaya, Titus Haryanto; Fadillah, Adil (LPPM Institut Bisnis dan Informatika Kesatuan, 2015)
This research is aimed to find out the influence of brand image toward customer loyalty of Teh Botol Sosro. The data used in this research were primary data. Samples were taken by Slovin fomula. Data processing and data analysis used SPSS program and double regression test.From double regression analysis, show that if brand image is 1 then the customer loyalty will increase 0,922 and ifproduct quality is 1 then the customer loyalty will increase 0,263. The result of correlation coeficient show r = 0,960, it means that there is a significant correlation bemeen brand image and product quality toward customer loyalty. The result of determination coeficient analysis show that brand image and product quality contributes 92,3% to customer loyalty and the other 7,7% is determined by otherfactors. Keywords : Brand Image, Product Quality, Customer Loyalty